METHODOLOGY OF ISLAMIC ECONOMIC STUDIES WITH SPECIAL EMPHASIS ON QUR’ANIC STUDIES - Seyyed Mofid Hossaini Kouhsari (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2023)
The methodology of Islamic economy is among the important areas of Islamic economic studies. The attention it gets from scholarstoday is much more than what it used to do in the past. Though it has certain backgrounds, it is a new study in this area. To deal withmethodology without paying attention to some of the foundations Islamic economic studies is a futile attempt devoid of any depthand precision. Giving attention to principles such as ‘the need for compatibility between methodologies, objectives and principles ofIslamic economy’, ‘the need for compatibility between legitimate goal and legitimate methodology’, ‘multi-methodological characteristic of Islamic economic’, ‘the stable and the variable in Islamic economy’, ‘guidelines and commandments (in Islamic economy)’, ‘the impact of time and place on (Islamic) economy’, ‘the impact of religion on Islamic economy’, ‘the role of intellect in deducing economic laws’ and ‘the presence of local and universal elements’, will further enrich methodological studies. Given these principles we can list the main methodologies of Islamic economy with special emphasis on Qur’anic economy as under: induction, extra-thematic interpretation, making use of descriptive statements of Islamic economy, endorsement, discovery, systematic, and establishment.